Comparison of school based and supplemental vaccination strategies in the delivery of vaccines to 5-19 year olds in Africa - a systematic review - Haddison, Eposi C. (F1000Res, 2017)
Background: Some vaccine preventable diseases (VPDs) still remain a public health burden in many African countries. The occurrence of VPDs in all age groups has led to the realization of the need to extend routine immunisation services to school age children, adolescents and adults. Supplemental immunisation activities (SIAs) and school based vaccinations (SBVs) are common strategies used to complement the expanded programme on immunisation (EPI). This review aimed to assess the effectiveness of SIAs compared to SBVs in the administration of vaccines to 5-19 year olds in Africa. Methods: Systematic review methods were used to address our study aim. Several electronic databases were searched up to March 30, 2017 for primary studies investigating the delivery of vaccines via SIAs or SBVs to 5-19 year olds. This search was complemented by browsing reference lists of potential studies obtained from search outputs. Outcomes considered for inclusion were: vaccination coverage, costs of the strategy or its effect on routine immunisation services. Results: Out of the 4938 studies identified, 31 studies met the review inclusion criteria. Both SIAs and SBVs showed high vaccination coverage. However, the SIAs reported higher coverage than SBVs: 91% (95% CI: 84%, 98%) versus 75% (95% CI: 67%, 83%). In most settings, SBVs were reported to be more expensive than SIAs. The SIAs were found to negatively affect routine immunisation services. Conclusions: Both SIAs and SBVs are routinely used to complement the EPI in the delivery of vaccines in Africa. In settings where school enrolment is suboptimal, as is the case in many African countries, our results show SIAs may be more effective in reaching school age children and adolescents than SBVs. Our results re-iterate the importance of evaluating systematic evidence to best inform African authorities on the optimal vaccine delivery strategies targeting school age children and adolescents.